(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
The conventional course of differentiated thyroid cancer (DTC) treatment requires surgical resection followed by radioactive iodine (131I) therapy (RAIT). Patients are advised to drink plenty of water, as 131I gets eliminated through the kidneys and the burden of extra radiation is reduced. Treating a case of DTC with chronic kidney disease (CKD) by RAIT is challenging. As a result, when planning hemodialysis in a DTC patient with CKD, the dose of 131I, the timing of the dialysis, and radiation safety must all be carefully considered. Because 131I is dialyzable, a standard Geiger counter can observe and detect it. A post-thyroidectomized case of DTC with CKD was successfully treated with 131I while continuing scheduled peritoneal hemodialysis (HD) simultaneously during hospital isolation, as reported here. This case report was aimed at sharing the HD management procedures, challenges to any adverse effects, and exposure doses of 131I-treated DTC patients in their immediate post-ablative days. Geiger counter measurements in the patient after HD following 131 I administration revealed levels of less than 4.20 Sv/h on the fifth day, allowing safe hospital discharge in this case. Bangladesh J. Nuclear Med. 26(1): 71-74, 2023